PROJECT OF MODERNISATION OF THE EDUCATION PROCESS IN SLOVAKIA - KORMANEC, Vladimir (Journal of Technology and Information Education, 2012)
The article deals with actual homochronous project of modernization of the primary and secondary educational process in Slovakia. It discusses the process of modernisation so far and reveals particular phases of project. The article outlines the main parts of the project, including its purpose project, its usage in practice.
Keywords: modernization of educational process; digital literacy; information and communication technologies